Analisis Perbedaan Tingkat Pemahaman Mahasiswa Akuntansi terhadap Konsep Dasar Akuntansi pada Mahasiswa Akuntansi di Perguruan Tinggi Se-Kota Madiun - Mahfudhi, Ali; Purbandari, Theresia; Immanuela, Intan (JRMA | Jurnal Riset Manajemen dan Akuntansi, 2018)
This research to demonstrate empirically the understanding of basic concepts of accounting differences between students from SMK Accounting Department, Department of Social Science High School, and High School Science Department at college accounting students throughout the city of Madiun. The data collection is done by spreading the questionnaire. The sample in this study was 82 accounting students in five universities, namely the Universitas Katolik Widya Mandala Madiun, STIE Dharma Iswara, IKIP PGRI Madiun, Universitas Merdeka, and Politeknik Negeri Madiun. The sampling technique used is convenience sampling and purposive sampling. Hypothesis testing using different test ONE WAY ANOVA with SPSS version 17. The results of this research that there is no difference between the understanding of the basic concepts of accounting students from SMK Accounting Department, Department of Social Science High School, and High School Science Department at college accounting students throughout the city of Madiun.